Socialization of the Utilization of Google Drive as an Online Storage Medium for Health Workers in Health Facilities - Mardi, Yuli; Dewi Oktavia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Google Drive is a free storage service provided by Google, where users can store files and access them anytime as long as their devices are connected to the internet. Google Drive can store various types of files such as documents, photos, audio, videos, and more. It offers 15GB of free storage capacity. With all its advantages, not all health workers are able to utilize Google Drive optimally. Conducting training on the use of Google Drive as an online storage tool for healthcare workers in health facilities is an essential step to ensure that all staff understand and can effectively use this technology. Besides boosting the productivity of healthcare workers, using Google Drive also allows them to provide better healthcare services to patients. This training will be conducted at the Kuranji Health Center in Padang over 2 days, consisting of both theoretical and practical sessions. The training was carried out successfully, and participants were able to learn about Google Drive and how to use it. The training participants included all health center staff who were not on active duty, such as medical record officers, pharmacy staff, midwives, doctors, and the head of the health center. Out of the 15 pretest questions related to Google Drive, the participants' average score was 69.55. After participating in the activity, their average score increased to 86.56. This indicates that the training conducted was effective in broadening the participants' understanding of Google Drive and the significant benefits offered by this Google service. In the future, it is hoped that similar training can be conducted with a longer duration.